Crystal structure of 2-[4-(4-chlorophenyl)-1-(4-methoxyphenyl)-2-oxoazetidin3-yl]benzo[de]isoquinoline-1, 3-dione dimethyl sulfoxide monosolvate. (February 2015) - Celik, Ismail; Akkurt, Mehmet; Jarrahpour, Aliasghar; Rad, Javad Ameri; Celik, Omer
No abstract available